2008 IEEE International Conference on Emerging Technologies and Factory Automation 2008
DOI: 10.1109/etfa.2008.4638512
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of magneto rheological fluid actuator enabling safe human-robot interaction

Abstract: Impedance control and compliant behavior for safe human-robot physical interaction of industrial robots normally can be achieved by using active compliance control of actuators based on various sensor data. Alternatively, passive devices allow controllable compliance motion but usually are mechanically complex. We present another approach using a novel actuation mechanism based on magneto-rheological fluid (MRF) that incorporates variable stiffness directly into the joints. In this paper, we have investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…They concluded that, in order to build a safety device capable of controlling the torque output of the robot joint axis and securing the holding torque in an emergency case, the proposed MR clutch was a promising candidate for practical implementation. Ahmed et al [24,25] developed a robot-arm system featuring an MR clutch/brake to accomplish a safe human-robot interaction, which is a type of compliance control. Fauteux et al [26] proposed a dual-differential rheological actuator (DDRA) to investigate the feasibility of high-performance robotic interactions, in which safety, robustness, and versatility are paramount.…”
Section: Mrf-based Robotsmentioning
confidence: 99%
“…They concluded that, in order to build a safety device capable of controlling the torque output of the robot joint axis and securing the holding torque in an emergency case, the proposed MR clutch was a promising candidate for practical implementation. Ahmed et al [24,25] developed a robot-arm system featuring an MR clutch/brake to accomplish a safe human-robot interaction, which is a type of compliance control. Fauteux et al [26] proposed a dual-differential rheological actuator (DDRA) to investigate the feasibility of high-performance robotic interactions, in which safety, robustness, and versatility are paramount.…”
Section: Mrf-based Robotsmentioning
confidence: 99%
“…The study of this subject has led to the study of new control and actuation mechanisms for robots. It has been shown that new actuation technologies are essential components of the future generations of human-safe robots [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…The study of this subject has led to the study of new control and actuation mechanisms for robots. It has been shown that new actuation technologies are essential components of the future generations of human-safe robots [1] [2].…”
Section: Introductionmentioning
confidence: 99%